FORM, METHODS AND TOOLS OF DEVELOPING A HEALTHY LIFESTYLE OF 8-9 CLASS STUDENTS - Abdunabiyev B. A. (Web of Journals Publishing, 2023)
This article provides information about the forms, methods and means of developing a healthy lifestyle of 8-9 graders and their practical results.
Keywords: development of physical education and sports, healthy generation, formation of a healthy lifestyle, interactive methods, methods and tools.